2005
DOI: 10.1128/aem.71.11.7531-7535.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate-Reducing Bacteria in Floating Macrophyte Rhizospheres from an Amazonian Floodplain Lake in Bolivia and Their Association with Hg Methylation

Abstract: Five subgroups of sulfate-reducing bacteria (SRB) were detected by PCR in three macrophyte rhizospheres (Polygonum densiflorum, Hymenachne donacifolia, and Ludwigia helminthorriza) and three subgroups in Eichhornia crassipes from La Granja, a floodplain lake from the upper Madeira basin. The SRB community varied according to the macrophyte species but with different degrees of association with their roots. The rhizosphere of the C 4 plant Polygonum densiflorum had higher frequencies of SRB subgroups as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…The correlation here between MeHg content and SRM abundance might further supported this point. In addition, our results are in accordance with previous studies suggesting that SO 4 2− concentration was also an important factor that governs Hg methylation capacity in the environment (Branfireun et al 1999;Acha et al 2005;Sitte et al 2010). High SO 4 2− content in the soils examined might be helpful to the prevalence of some SRM that produced MeHg (Han et al 2010), and this could explain partially why the SO 4 concentration are significantly correlated to the MeHg content.…”
Section: Resultssupporting
confidence: 92%
“…The correlation here between MeHg content and SRM abundance might further supported this point. In addition, our results are in accordance with previous studies suggesting that SO 4 2− concentration was also an important factor that governs Hg methylation capacity in the environment (Branfireun et al 1999;Acha et al 2005;Sitte et al 2010). High SO 4 2− content in the soils examined might be helpful to the prevalence of some SRM that produced MeHg (Han et al 2010), and this could explain partially why the SO 4 concentration are significantly correlated to the MeHg content.…”
Section: Resultssupporting
confidence: 92%
“…and Desulfonema spp.). Desulfobulbus propionicus, the closest match to the representative sequence from the cluster analysis, has been shown to methylate Hg under sulfatereducing and/or fermentative conditions (King et al 2000, Benoit et al 2001, Kerin et al 2006, Rodríguez-González et al 2009), is often found in high abundances where MeHg is present (Achá et al 2005) and has been shown to have a positive net MeHg production (Bridou et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While these bacteria are primarily anaerobic, there are sulfate-reducing members of the class Deltaproteobacteria that will survive and grow under oxic conditions (Krekeler et al 1997, Sigalevich & Cohen 2000, Sigalevich et al 2000a. Although the aerobic metabolism of these organisms involves oxidation of sulfide and sulfite, when conditions become void of oxygen, anaerobic respiration commences, including sulfatereduction (Sigalevich et al 2000b), which may facilitate Hg methylation in surface sediments (Achá et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Desulfovibrios facilitate metal corrosion (Neria-Gonzalez et al, 2006) and have been repeatedly isolated from oil and gas production facilities (Miranda-Tello et al, 2003;Magot et al, 2004). Desulfovibrio ribosomal gene sequences have been retrieved from submerged mine timbers (Labrenz & Banfield, 2004), gas hydrate mounds (Mills et al, 2003) and floating macrophyte rhizospheres (Acha et al, 2005), while desulfovibrio-specific dissimilatory sulfite reductase genes (dsrAB) have been recovered from temperate sulfiderich streams (Elshahed et al, 2003) and frozen Antarctic lakes (Karr et al, 2005).…”
mentioning
confidence: 99%